2017
DOI: 10.1158/1541-7786.mcr-16-0374
|View full text |Cite
|
Sign up to set email alerts
|

Nucleome Analysis Reveals Structure–Function Relationships for Colon Cancer

Abstract: Chromosomal translocations and aneuploidy are hallmarks of cancer genomes; however, the impact of these aberrations on the nucleome (i.e., nuclear structure and gene expression) is not yet understood. Here, the nucleome of the colorectal cancer cell line HT-29 was analyzed using chromosome conformation capture (Hi-C) to study genome structure, complemented by RNA sequencing (RNA-seq) to determine the consequent changes in genome function. Importantly, translocations and copy number changes were identified at h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…spatial segregation of active and inactive regions of the genome, topologically associating domains (TADs), and associated peaks of contact frequency (often referred to as loops) [1,[3][4][5]. Hi-C maps have helped implicate changes in genome organization in a variety of disorders, including acute lymphoblastic leukemia [6], colorectal cancer [7], and limb development disorders [8]. More fundamentally, they provide insights into the mechanisms by which genome conformation structures arise, are maintained, and change over time [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…spatial segregation of active and inactive regions of the genome, topologically associating domains (TADs), and associated peaks of contact frequency (often referred to as loops) [1,[3][4][5]. Hi-C maps have helped implicate changes in genome organization in a variety of disorders, including acute lymphoblastic leukemia [6], colorectal cancer [7], and limb development disorders [8]. More fundamentally, they provide insights into the mechanisms by which genome conformation structures arise, are maintained, and change over time [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Biologists are interested in uncovering the mechanisms that drive global and local folding to better understand the vast and complex gene regulation network. This aids comprehension of the functional diversity of cells and how changes in the spatial conformation of the genome can cause diseases [24, 32, 40]. …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that rearrangements in cancer not only alter the one-dimensional (1D) but also the three-dimensional (3D) structure of the genome and individual chromosomes (Engreitz et al 2012;Ay et al 2015; Barutcu et al 2015;Harewood et al 2017;Seaman et al 2017). These studies were made possible by the development of high-throughput chromosome conformation capture techniques (e.g., Hi-C) (Lieberman-Aiden et al 2009;Rao et al 2014), which also revealed novel relationships between spatial arrangement of the genome and its function (Dixon et al 2012;Ay et al 2014;Pope et al 2014;Sexton and Cavalli 2015).…”
Section: Introductionmentioning
confidence: 99%